2010
DOI: 10.1016/j.ijid.2010.02.2238
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of abscesses and self-treatment among injection drug users in Tijuana, Mexico

Abstract: Summary Background Soft tissue infections are common among injection drug users (IDUs), but information on correlates and treatment in this highly marginalized population is lacking. Methods Six hundred twenty-three community-recruited IDUs in Tijuana, Mexico, completed a detailed interview on abscess history and treatment. Univariate and multiple logistic regressions were used to identify factors independently associated with having an abscess in the prior 6 months. Results Overall, 46% had ever had an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
5
40
2
Order By: Relevance
“…The use of these approaches could have resulted in the over-sampling of higher-risk individuals. Similar levels of symptoms to those reported here have been found in studies from other countries [12,26]. Overall a quarter of the PWID participating in this study had sought advice from a doctor or nurse about one of the three symptoms enquired about in the study.…”
Section: Symptoms Of Injection-related Bacterial Infectionssupporting
confidence: 82%
“…The use of these approaches could have resulted in the over-sampling of higher-risk individuals. Similar levels of symptoms to those reported here have been found in studies from other countries [12,26]. Overall a quarter of the PWID participating in this study had sought advice from a doctor or nurse about one of the three symptoms enquired about in the study.…”
Section: Symptoms Of Injection-related Bacterial Infectionssupporting
confidence: 82%
“…[7][8][9][10][11][12][13][14]23,26,46,48,49 Previous studies along Mexico's North Border have contributed to this international consensus by identifying a panoply of associations between criminal justice experiences and behavioral risk factors, including syringe sharing. 29,50,51 We have also observed independent associations between arrest and HIV status. 30 This study extends previous research on the links between experiencing extra-judicial police practices with HIV infection 18 by demonstrating a full range of behavioral and health factors associated with syringe confiscation and thus strengthening the evidence base on the health-human rights nexus.…”
Section: Discussionsupporting
confidence: 60%
“…This parallels previous research in this region, highlighting the role of actual and perceived police practices as facilitators of risk behaviors and barriers to protective behaviors, including pharmacy-based syringe access. 18,29,33,36,50,52,53 Women in this sample may encounter additional risks stemming from syringe confiscation in the realm of sexual transmission. Literature suggests that police officers often use drug and syringe possession and commercial sex activity to extort sexual services, 2,5,16,18,51,54 a paradigm clearly accentuated by our finding that syringe confiscation was independently associated with police sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…A Yes have assessed healthcare-seeking behaviour: in Mexico, only 12% of IDU sought formal treatment for skin abscesses 31 ; in Miami, many chronic drug users reported 'attitudinal and behavioural barriers' to health care, such as not wanting treatment or self-treating 32 ; and in India, 33% of IDU did not seek formal healthcare services. 33 The latter, however, was to our knowledge the only study to analyse social and structural factors and found that low utilization of healthcare services was associated with exposure to policing, social exclusion and negative healthcare experiences.…”
Section: A Nomentioning
confidence: 99%